The Effectiveness of Information and Communication Technology in Enhancing Islamic Education Learning in the Contemporary Era - Gania Godelova Koto, Gita (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
The utilization of Information and Communication Technology (ICT) in learning Islamic Religious Education (PAI) in the contemporary era has become a major highlight in the world of Education. This study aims to determine the extent to which the level of effectiveness of ICT in improving learning PAI in the contemporary era today. This research adopts the method of literature study or literature review to explore this theme. The research steps include topic identification, literature collection, literature selection based on relevance and quality, as well as in-depth analysis to identify key findings, Approaches, Methodologies, and related research results. From the synthesis of the literature, conclusions were drawn regarding the effectiveness of the use of ICT in PAI learning in the contemporary era, with recommendations for subsequent research. The results showed that the integration of ICT in PAI learning provides the potential to increase the effectiveness of learning, enrich the learning experience of students, and expand the scope of Islamic education paradigm.